The need for accurate measurements of thermal velocity distribution functions in the solar wind - Wilson, Lynn B.; Goodrich, Katherine A.; Turner, Drew L.; Cohen, Ian J.; Whittlesey, Phyllis L.; Schwartz, Steven J. (Frontiers in Astronomy and Space Sciences, 2022)
The current state of the art thermal particle measurements in the solar wind are insufficient to address many long standing, fundamental physical processes. The solar wind is a weakly collisional ionized gas experiencing collective effects due to long-range electromagnetic forces. Unlike a collisionally mediated fluid like Earth's atmosphere, the solar wind is not in thermodynamic or thermal equilibrium. For that reason, the solar wind exhibits multiple particle populations for each particle species. We can mostly resolve the three major electron populations (e.g., core, halo, strahl, and superhalo) in the solar wind. For the ions, we can sometimes separate the proton core from a secondary proton beam and heavier ion species like alpha-particles. However, as the solar wind becomes cold or hot, our ability to separate these becomes more difficult. Instrumental limitations have prevented us from properly resolving features within each ion population. This destroys our ability to properly examine energy budgets across transient, discontinuous phenomena (e.g., shock waves) and the evolution of the velocity distribution functions. Herein we illustrate both the limitations of current instrumentation and why higher resolutions are necessary to properly address the fundamental kinetic physics of the solar wind. This is accomplished by directly comparing to some current solar wind observations with calculations of velocity moments to illustrate the inaccuracy and incompleteness of poor resolution data.